2021
DOI: 10.1177/0192513x211064863
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Food and Food Behaviors in Intimate Partner Violence

Abstract: There is a paucity of research that systematically examines how food behaviors play a role in intimate partner violence (IPV). Therefore, this qualitative study aims to answer the broad question, what role do food behaviors play in intimate relationships? Food behavior narratives emerging from participants of court-mandated domestic violence (DV) offender treatment programs were analyzed using grounded theory methods. Five themes emerged. Two described inflammatory/harmful roles: (1) food as a trigger for ange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Regarding relational components, perpetrators may use food as an indicator of gender role performance and as such, food will act as a trigger for inflicting IPV. Lack of food can inflame violence, while food offers can quell it (Shimizu et al, 2021). IPV affects ability to work, which increases food insecurity, which can then lead to an increase in IPV (Chilton et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding relational components, perpetrators may use food as an indicator of gender role performance and as such, food will act as a trigger for inflicting IPV. Lack of food can inflame violence, while food offers can quell it (Shimizu et al, 2021). IPV affects ability to work, which increases food insecurity, which can then lead to an increase in IPV (Chilton et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Sample size ranged from 12 (Clark & Jordan, 2022) to 69,072 (Ackerson & Subramanian, 2008); as expected, qualitative studies tended to have smaller samples than did quantitative studies. Almost all studies relied on self-reported IPV; an exception is Shimizu and colleagues (2021), who used observations of participants in court-mandated domestic violence offender treatment programs. Similarly, almost all studies relied on self-reported food insecurity; exceptions included a few studies that used biological measures such as BMI and anemia (Ackerson & Subramanian, 2008; Adhikari et al, 2020; Ferdos & Rahman, 2018; Rahman et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation